The Economic characteristics of the female population in Baghdad Governorate - Najm, Noor (Al-Adab Journal, 2025)
The economic characteristics of females are among the vital topics that deserve study and analysis, given their increasing role in the economy. This research addresses the economic characteristics of the female population aged 15 and above in Baghdad Governorate (1997-2016) with the aim of understanding the demographic structure and distribution. The study was carried out over a period, encompassing two main axes: the first axis covers the theoretical framework, while the second axis focuses on the spatial differences in the economic characteristics of the female    population by district in Baghdad Governorate.The results of the research showed a significant increase in the percentage of females involved in economic activities in the governorate from 10% in1997 to 17% in 2016. Additionally, the study found a significant increase in female unemployment rates during the study period. The research also indicated that females entering the labor market are influenced by a set of social and economic factors, with spatial distribution being linked to the extent of women’s presence in society, their educational levels, and the roles they undertake in economic activities.